Global analysis of the determinants of systemic risk during the Global Financial Crisis of 2008 and the European Sovereign Debt Crisis - Henzler, Dominik (2021)
This Dissertation aims to provide a differentiated answer to the research question “What drives banks’ contribution to systemic risk during periods of financial turmoil?” This research also distinguishes between contribution to local and contribution to global systemic risk in order to shed light on how banks’ contribution to systemic risk differs across various regions. A sample of international banks covering 39 countries is analyzed for this purpose. The selected crisis periods are the Global Financial Crisis around the collapse of Lehman Brothers in 2008, as well as the first and the second peak of the European Sovereign Debt Crisis in 2010 and 2011 respectively. Supporting conjectures from earlier risk literature, several bank-specific accounting variables are found to enable banks’ contribution to systemic risk during the Global Financial Crisis in 2008. More precisely, the size of a bank and its market-to-book ratio are found to be positively related to systemic risk while a bank’s profitability is found to be negatively related. In addition, more powerful regulatory supervisors are found to be negatively related to systemic risk while greater capital stringency imposed by regulators is found to be negatively related to systemic risk. However, most of the variables lose their statistical significance during the European Sovereign Debt Crisis, which supports previous findings suggesting that drivers of systemic risk vary over crisis periods and might even be unique to each crisis episode.